Explaining Economic Growth in China: Testing Sociological Tools for Validity - Kurakin, Alexander (Journal of Economic Sociology, 2014)
Today it makes little sense to ask a question, why social scholars are interested in China’s economy as far as the answer is obvious. The growth rate of Chinese economy and duration of its growth period are stunning. It is likely that in the nearest future China will outrun USA in terms of GDP and become the largest economy in the world. Moreover, China has made a huge progress in GDP per capita. But this is not the only reason for the great interest in China. Chinese communist party is still in power. By the standards of the Western democracies, China remains to be an authoritarian state. Taken together, those statements make a paradox: how could communists produce so huge economic growth? Recent history of socialist countries seems to show that it is impossible. Though the Soviet Union sometimes demonstrated fast growth, it couldn’t keep the pace for a long period. In Chinese case, we face a more fundamental phenomenon than just mobilization of a country in order to achieve vital objectives (usually with high costs). “Capitalism from Below: Markets and Institutional Change in China” by Viktor Nee and Sonja Opper suggests the answer for this question [Nee, Opper 2012].